Pengaruh Stres Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Pelayaran Papua Mitra Samudra Sorong - Ling Sie Ni; Yuliana Yuliana; Arwin; Tasik Utama; Weny Weny (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the effect of work stress on employee productivity at PT Pelayaran Papua Mitra Samudra Sorong. The research method used is a quantitative method with an associative approach. The population is 30 employees of PT Pelayaran Papua Mitra Samudra Sorong and all of them are used as research samples. The data analysis method consists of the correlation coefficient test, the coefficient of determination test, the simple linear regression test and the Z test. The correlation coefficient test results show a correlation value (r) of 0.571, which means that work stress, has a direct and moderate relationship with employee work productivity. In the results of the coefficient of determination test, work stress has an effect on work productivity of 32.6% while the remaining 67.4% is influenced by factors not examined in this study. And on the results of hypothesis testing, it is known that Zcount 3,08 > Ztable 1,96, so it can be concluded that work stress has a significant effect on employee work productivity at PT. Papua Mitra Samudra Sorong.